2017
DOI: 10.1513/annalsats.201701-081oc
|View full text |Cite
|
Sign up to set email alerts
|

A Geospatial Epidemiologic Analysis of Nontuberculous Mycobacterial Infection: An Ecological Study in Colorado

Abstract: Rationale: Nontuberculous mycobacteria (NTM) are ubiquitous environmental microorganisms. Infection is thought to result primarily from exposure to soil and/or water sources. NTM disease prevalence varies greatly by geographic region, but the geospatial factors influencing this variation remain unclear.Objectives: To identify sociodemographic and environmental ecological risk factors associated with NTM infection and disease in Colorado. Methods:We conducted an ecological study, combining data from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…Yet, soil components such as natural rock, sand, or clay may also impact NTM presence and diversity. A study by Lipner et al reported increasing clay concentrations as protective against NTM, while increasing silt concentrations was associated with NTM infection (11). In this same study and another, higher manganese concentration was associated with disease prevalence (9,11).…”
Section: Downloaded Fromsupporting
confidence: 65%
“…Yet, soil components such as natural rock, sand, or clay may also impact NTM presence and diversity. A study by Lipner et al reported increasing clay concentrations as protective against NTM, while increasing silt concentrations was associated with NTM infection (11). In this same study and another, higher manganese concentration was associated with disease prevalence (9,11).…”
Section: Downloaded Fromsupporting
confidence: 65%
“…68 Another factor that appears to influence risk of PNTM is the watershed affiliated with a patient's area of residence. 69 Using data on non-CF NTM patients treated at National Jewish Health and residing in Colorado, researchers found that three specific watersheds were at increased risk of PNTM, all of which appear to share a similar water source and distribution mechanism. 69 Soil and dust have also been identified as potential sources of NTM exposure.…”
Section: Pntm Risk Factorsmentioning
confidence: 99%
“…69 Using data on non-CF NTM patients treated at National Jewish Health and residing in Colorado, researchers found that three specific watersheds were at increased risk of PNTM, all of which appear to share a similar water source and distribution mechanism. 69 Soil and dust have also been identified as potential sources of NTM exposure. Aerosols generated from potting soils in households of PNTM patients were found to contain known pathogenic NTM species, including M. avium, M. intracellulare, and M. kansasii, some of which matched corresponding patient isolates by pulsed-field gel electrophoresis genotyping.…”
Section: Pntm Risk Factorsmentioning
confidence: 99%
“…Aquatic environments can be significant NTM reservoirs, and water is increasingly recognized as an important NTM transmission medium. The aquatic environments in which NTM reside can be as small as a showerhead or as large as a watershed (46). The aquatic microenvironments in which NTM have been found are largely of human origin: NTM-containing water supplies have been responsible for outbreaks of NTM disease in hospitals (47,48), as well as for outbreaks among footbath customers (49,50), metal workers (51,52), and alternative-medicine users (53).…”
Section: The Aquatic Lives Of Nontuberculous Mycobacteriamentioning
confidence: 99%
“…Environmental sampling revealed that mycobacteria comprised 1/3 of all microbes in the water of an indoor pool and 8/10 of all microbes in the surrounding bioaerosol (55). The aquatic macroenvironments in which NTM have been found include those of human origin (e.g., municipal water supplies) (56-59) but also natural watersheds (46) and lakes (60,61). Data from experimental models suggest that the water flow in aquatic micro-and macroenvironments is insufficient to prevent the formation of NTM biofilms (62), which facilitate NTM survival in numerous hostile environments (63).…”
Section: The Aquatic Lives Of Nontuberculous Mycobacteriamentioning
confidence: 99%